Investigation of environmental ethics, spiritual health, and its relationship with environmental protection behaviors in nursing students - Saeed Jadgal, Mohammad; Bamri, Abdulwahid; Fattahi Ardakani, Mojtaba; Jadgal, Nasir; Zareipour, Moradali (Investigación y Educación en Enfermería, 2024)
Objective. To investigate the relationship between environmental ethics, spiritual health, and environmental behavior among nursing students. Methods. In this cross-sectional study, 200 iranian students from the Chabahar Nursing School were selected using a simple random sampling method. The data collection tool included a questionnaire on demographic information, knowledge, attitudes and behaviors towards the environment, environmental ethics, and spiritual health. Partial least squares structural equation modeling (PLS-SEM) was utilized to evaluate the conceptual framework in this study. Results. The mean score for environmental ethics among nursing students was 65.73±10.61 out of 100. Most of the students (47%) had desirable environmental ethics. The knowledge structure (β=0.46) predicted attitude. The attitude structure also predicted environmental behavior (β=0.28) and spiritual health (β=0.31). Ultimately, the results showed that spiritual health and environmental ethics predict environmental behavior directly and indirectly (p<0.001). Conclusion. Spiritual health and environmental ethics were strong predictors of environmental behavior. Therefore, it is necessary to take into account not only students’ spiritual health but also their ethical behaviors to promote environmental protection behaviors in the future.